Hematoma in aesthetic surgery: tips to avoid unaesthetic results Hyaluronidase and hematoma drainage - Ada Regina Trindade de Almeida; Renata Sitonio T. D. Monteiro (Sociedade Brasileira de Dermatologia (SBD), 2021)
Hematomas are common following cosmetic surgery. When minor, they are treated with observation only as they are most often reabsorbed. However, even with small collections of blood, if no early intervention is adopted, poor aesthetic outcomes may occur. Early drainage has been especially described in otorhinolaryngology and radiology journals. The authors present an approach to early treating hematomas. Special emphasis is given to the use of hyaluronidase, which is well known by dermatologists and plastic surgeons for its ability to dissolve hyaluronic acid, but its utility in the treatment of hematomas is not so commonly known by these experts.